Economic Tomography: Opportunity to Foresee and Respond to Socio-Economic Crises - Kuklin, Aleksandr Anatolyevich; Bystray, Gennadiy Pavlovich; Okhotnikov, Sergey Aleksandrovich; Vasilyeva, Elena Vitalyevna (Economy of Regions, 2015)
In the article, the approach based on the authors’ hypothesis is considered: the development of Russia has specific characteristics (on the one hand, its size, mentality and certain closed nature of its economy, on the other hand, the considerable dominating resource and human potential, and, as the result, its real role in the world economic community). The diagnostics of these characteristics (at the level of the individual’s welfare and territory of accommodation) reveals crises, estimates threats to region socio-economic development at early stages and helps to evaluate the state of a region for 3-5 years. In other words, managers have time necessary for rapid response to the crisis phenomena and administrative mistakes, for decreasing the impact of the arising threats. The purpose of the article is to present the theoretical and methodological tools of the appearing threats recognition at their early stages, which allows to enter the crisis period with smaller losses. Computational experiments to classify the prior socio-economic crises have been conducted (9 possible options are considered), the trajectories of change of the main indicators of the individual’s welfare and territory of residence influenced by various factors are digitized. On the basis of the proposed approach (named as the economic tomography), the attempt of the comprehensive assessment of the state of Russian typical representative regions is made.